Guillain-Barré syndrome related to Zika virus infection: A systematic review and meta-analysis of the clinical and electrophysiological phenotype - Leonhard, Sonja E.; Bresani-Salvi, Cristiane C.; Lyra Batista, Joanna D.; Cunha, Sergio; Jacobs, Bart C.; Brito Ferreira, Maria Lucia; P. Militão de Albuquerque, Maria de Fatima (PLOS Neglected Tropical Diseases, 2020)
Author summary Guillain-Barré syndrome (GBS) is a rare but severe neurological disease, characterized by an acute onset flaccid paralysis. GBS is thought to be caused by an exaggerated immune response to common infections that damages the peripheral nerves. The Zika virus (ZIKV) is the most recent pathogen to be connected to GBS, when large outbreaks of ZIKV infection in French Polynesia and Latin America were followed by an increased incidence of GBS patients. To better understand the clinical features and outcome of ZIKV-related GBS, we have performed a systematic review and meta-analysis of all published studies on GBS related to ZIKV. We identified 35 studies, reporting on a total of 601 patients with GBS and a suspected, probable or confirmed Zika virus infection, and were able to summarize data of 587 patients from 21 studies in a pooled analysis. Our study shows that published cases with ZIKV-related GBS generally have both sensory and motor symptoms, facial palsy, demyelination on electrophysiological examination, and a severe disease course that often necessitates ICU admittance. The relatively long time between infectious and neurologic symptoms and the lack of detection of viral particles in bodily fluids in most patients suggest a post-infectious rather than an infectious pathogenesis. However, these results should be interpreted taking into account the heterogeneity between studies, which was considerable for many variables, and a possible reporting bias of more severe cases. Outbreaks of ZIKV and GBS may appear in the future and our study can help clinicians in diagnosing and managing GBS patients in ZIKV endemic areas, and increases our understanding of the neuropathology of ZIKV.